A REFLECTIVE STUDY ON SEXUAL EDUCATION AS AN INTEGRAL ELEMENT OF DAILY SCHOOL LIFE - Barbosa de Sousa Júnior, José (Revista Gênero e Interdisciplinaridade, 2024)
This article presents a reflective analysis of sexual education as an essential component of everyday school life. Exploring the integration of sexual education into the daily practices of the school through a qualitative and exploratory approach, utilizing specialized literature in the virtual environment, the research examines the importance and impact of this approach on students' development. The study aims to highlight different perspectives on sexual education, emphasizing the need for a reflective and inclusive approach. By addressing the relevance of sexual education in the school context, the study seeks to identify educators' approaches to sexual education, assessing whether or not this topic is being incorporated. Additionally, it aims to understand the perspectives of students and their parents regarding this type of education, contributing to a better understanding of how this dimension can enrich the educational experience and promote a school environment that is more informed, healthy, and supportive of diversity.